Do Japanese Candlestick Patterns Help Identify Profitable Trading Opportunities? An Analysis on Selected Forex Markets - Ameen, Aisha Ahmed (2013)
Japanese candlestick charts were first introduced to the Western world in 1989 by Steve Nison. No one in the West got to know about the Japanese technical analysis before the first edition of his textbook, and no charting packages included them either prior to the first edition. Japanese candlestick patterns have become very popular since then. Japanese candlestick patterns are technical trading rules that are used to predict price directions based on the relationship between opening, high, low and closing prices. Currently many market participants are implementing Japanese candle patterns as part of their robust trading systems. This research examines the profitability of four bullish and four bearish Japanese candlestick reversal patterns in seven foreign exchange currencies which represent both advanced and emerging foreign currency markets. These currencies include AUD/USD, USD/CAD, EUR/USD, GBP/USD, USD/INR, USD/JPY and USD/ZAR. The sample covers a 12-year span of 3,129 observations. The statistical z score test is used to test the statistical significance of the returns at 5% level for seven holding periods. The RSI is used with three candle patterns to further filter the results. The findings show strong evidence of some profitable candlestick reversal patterns in foreign currency markets.